Development of Load Balancing Methodology in Cloud Computing Platforms - Mohammed Khairullah Mohsin, Mustafa A. Fiath (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Load balancing is the process of distributing customer tasks among multiple computing resources, such as virtual machines (VMs), servers and networks. It is a major concern in cloud computing as the number of customer demanding the service is growing exponentially. An efficient load balancing approach can detect the load of the VMs proactively and assigns the customer tasks to the VMs accordingly. In this paper, we present a mechanism on load balancing in cloud using probability theory. The main aim of the proposed approach is to reduce the standard deviation of the load between the virtual machines so that they are close to zero.